2008
DOI: 10.1200/jco.2008.16.3956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prospective and Retrospective Indicators of the Quality of End-of-Life Cancer Care

Abstract: A B S T R A C T PurposeTo compare prospectively and retrospectively defined benchmarks for the quality of end-of-life care, including a novel indicator for the use of opiate analgesia. MethodsLinked claims and cancer registry data from 1994 to 2003 for New Jersey and Pennsylvania were used to examine prospective and retrospective benchmarks for seniors with breast, colorectal, lung, or prostate cancer who participated in state pharmaceutical benefit programs. ResultsUse of opiates, particularly long-acting opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 26 publications
5
76
1
Order By: Relevance
“…Indicators for quality of EOL cancer care in the last month of life included chemotherapy, prolonged hospitalization, multiple ER visits, ICU care, and administering CPR, intubation, and mechanical ventilation. Taiwanese cancer patients cared for by a medical oncologist in the last month of life were more likely than patients whose primary physicians were other specialists to be treated closer to death with chemotherapy, consistent with recent reports from western countries [3,16,26,35]. Medical oncologists had a better knowledge of the role of chemotherapy in metastatic cancer than other specialist groups [36] and held more optimistic attitudes toward adjuvant chemotherapy [18,37] and the palliative benefit of chemotherapy [36,38].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Indicators for quality of EOL cancer care in the last month of life included chemotherapy, prolonged hospitalization, multiple ER visits, ICU care, and administering CPR, intubation, and mechanical ventilation. Taiwanese cancer patients cared for by a medical oncologist in the last month of life were more likely than patients whose primary physicians were other specialists to be treated closer to death with chemotherapy, consistent with recent reports from western countries [3,16,26,35]. Medical oncologists had a better knowledge of the role of chemotherapy in metastatic cancer than other specialist groups [36] and held more optimistic attitudes toward adjuvant chemotherapy [18,37] and the palliative benefit of chemotherapy [36,38].…”
Section: Discussionsupporting
confidence: 73%
“…These findings are different from the majority of published reports in the literature. Although one study demonstrated that generalists and oncologists showed similar care practices for referral to hospice care [25], other studies indicated that cancer patients cared for by a medical oncologist were significantly more likely to be enrolled in hospice care [14,17,23,26] but to be referred to hospice care closer to death [14,24] than cancer patients whose primary physician was another specialist. The discrepancy between our findings and those in the literature may come from two counterbalancing forces related to the characteristics and experiences of medical oncologists in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As 39 % of all relatives did not return the questionnaire, the results could be subjected to selection bias as well [18]. Nonetheless, a retrospective approach is a well-accepted study design in the examination of care at the EOL [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these measures are well suited for comparing systems of care, 34 and recent data suggest that they provide comparable information to measures collected from medical record abstractions, collected either prospectively or retrospectively. 35,36 Moreover, some have questioned the validity of retrospective studies of end-of-life care for cancer patients because it is not always possible to identify the point at which physicians perceive patients' terminal status. 37 However, we studied patients diagnosed with metastatic lung and colorectal cancer, so all patients were known to have poor prognoses and limited life expectancy.…”
Section: Discussionmentioning
confidence: 99%